2021
DOI: 10.1101/2021.02.12.21250941
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Phenome-wide Consequences of Anorexia Nervosa Genes

Abstract: Anorexia nervosa (AN) is a psychiatric disorder with complex etiology, with a significant portion of disease risk imparted by genetics. Traditional GWAS studies produce principal evidence for the association of genetic variants with disease, and provide a jumping-off point for downstream functional analyses. Transcriptomic imputation (TI) allows for the translation of SNPs into regulatory mechanisms, which can then be used to assess the functional outcome of genetically regulated gene expression (GReX) in a mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 95 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…A PheWAS functionally queries an electronic health record (EHR) to identify associations of a trait of interest (i.e., AN) with the clinical phenome (i.e., all of the disease and medication codes included in the EHR). Exploring the phenotypic associations with AN genetic architecture can isolate how GWAS variants functionally contribute to AN disease risk, symptomatology, and clinical presentation [19]. Several PheWAS of AN are currently underway.…”
Section: The Endocrinological and Metabolic Setting Of Anmentioning
confidence: 99%
“…A PheWAS functionally queries an electronic health record (EHR) to identify associations of a trait of interest (i.e., AN) with the clinical phenome (i.e., all of the disease and medication codes included in the EHR). Exploring the phenotypic associations with AN genetic architecture can isolate how GWAS variants functionally contribute to AN disease risk, symptomatology, and clinical presentation [19]. Several PheWAS of AN are currently underway.…”
Section: The Endocrinological and Metabolic Setting Of Anmentioning
confidence: 99%
“…However, it is still possible that there are undiagnosed patients included in the analysis as the BioMe TM Biobank. For example, an individual may not have a EHR record of AN in the BioMe TM Biobank if (s)he had an ANrelated visit at another healthcare facility or when they were adolescents 7 (the youngest individual included in this study is 25 years old). Given the low prevalence of AN (~1%) 41 and our exclusion of all individuals with any ED diagnosis, we expect the impact of diagnostic contamination should be minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical & epidemiological studies have found a range of psychiatric (e.g., stress, depression, trauma, anxiety 26,27 ), lifestyle (e.g., smoking, 28,29 sedentary behaviour 30,31 ) and socioeconomic factors (e.g., income & education levels 32,33 ) associated with an increased risk of chronic pain, while medical conditions such as obesity 34 & cardiovascular diseases 35,36 are also common comorbidities. 37 Large-scale GWAS have identified specific genetic loci in chronic pain conditions (e.g., back, 12,19 neck/shoulder, 15 knee pain 9 & widespread pain 14,20 ) and demonstrated shared genetic bases with biopsychosocial traits (e.g., depression, 19,20,27 post-traumatic stress disorder, 20 anorexia nervosa, 38 asthma, 20 brain morphology, 18 poor sleep, 8,19,39 obesity, 5 low educational attainment 19,40 & smoking 19,40 ). However, the nature of causal relationships between common chronic pain conditions and such multidimensional factors remains to be comprehensively examined.…”
Section: Introductionmentioning
confidence: 99%